2015
DOI: 10.1242/jcs.148296
|View full text |Cite
|
Sign up to set email alerts
|

PML induces compaction, TRF2 depletion and DNA damage signaling at telomeres and promotes their alternative lengthening

Abstract: The alternative lengthening of telomeres (ALT) mechanism allows cancer cells to escape senescence and apoptosis in the absence of active telomerase. A characteristic feature of this pathway is the assembly of ALT-associated promyelocytic leukemia (PML) nuclear bodies (APBs) at telomeres. Here, we dissected the role of APBs in a human ALT cell line by performing an RNA interference screen using an automated 3D fluorescence microscopy platform and advanced 3D image analysis. We identified 29 proteins that affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 77 publications
2
85
0
1
Order By: Relevance
“…Consistent with the view that replication stress and misguided DNA repair synthesis are crucial features of ALT, it was found that inhibition of ATR or ATM decreases ALT activity (3, 10, 17, 18). However, except for the Flynn et al study, no immediate ALT-specific effects after ATR and/or ATM inhibition on cell viability and proliferation on the time scale of several days have been reported.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Consistent with the view that replication stress and misguided DNA repair synthesis are crucial features of ALT, it was found that inhibition of ATR or ATM decreases ALT activity (3, 10, 17, 18). However, except for the Flynn et al study, no immediate ALT-specific effects after ATR and/or ATM inhibition on cell viability and proliferation on the time scale of several days have been reported.…”
Section: Resultssupporting
confidence: 74%
“…In addition to the full-length ATRX band at about 260 kDa, shorter ATRX variants between 200 and 220 kDa were also detected in the HA blot that might correspond to degraded or alternatively spliced products of ATRX, as described previously (15, 16). (B) Average number of APBs per cell in uninduced and for 7 days induced U2OS ATRX-1 cells ( n  = 350) analyzed by 3D confocal image analysis of PML immunofluorescence and telomere FISH stainings as described previously (10). (C) C-circle assay as a marker of ALT activity in uninduced and induced U2OS ATRX-1 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ALT cancer cells, ALT-associated promyelocytic leukemia (PML) bodies specifically localize to telomeres to form ALT-associated PML bodies (APBs), which are important for recombination-based telomere elongation184142. To determine whether TPP1 ΔOBRD overexpression, knockdown of ATRX or/and DAXX could transform telomerase-positive HTC75 cells into ALT-like cells, we used immunofluorescence and fluorescent in situ hybridization (IF-FISH) to detect APBs formation in different cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The NuRD chromatin remodeling complex together with the zinc-finger protein ZNF827 lead in ALT cells to decreased shelterin binding, hypoacetylation of telomeric chromatin, enhanced telomere-telomere interactions and recruitment of HR proteins, creating an environment that promotes recombination and ALT activity. PML as component of the APBs induces clustering and compaction of colocalized telomere repeats, shelterin TRF2 depletion and DDR at telomeres and promotes ALT by changing the telomeric chromatin state [138]. Histone deacetylase HDAC9 regulates ALT activity by formation of APBs and C-circles in ALT positive cells and upon depletion in ALT cell lines the replicative capacity were compromised [139].…”
Section: Epigenetic Regulation Of Tmmsmentioning
confidence: 99%